Leptin Level Expression in Obese Women During Chronic Physical Exercise - Anwardi, Nandina Salsa Billa; Sugiharto, Sugiharto (Indonesian Conditioning Coaches, 2025)
This study aims to analyze the effect of short-term combination training for 4 weeks in reducing leptin levels in obese women. The method used is a true experimental with a randomized pretest-posttest control group design, involving 14 obese female subjects who were divided into two groups: control (K1) and combination training (K2). The combination training consisted of endurance training (treadmill) and resistance with moderate intensity (60-70% 1-RM) which was done 5 times per week for 4 weeks. The results showed a significant decrease in leptin levels in the K2 group compared to K1, which actually showed a slight increase in leptin. The decrease in leptin levels in K2 was associated with a decrease in fat mass and body mass index (BMI), accompanied by an increase in muscle mass. Combination training has a significant effect on reducing leptin through increased energy expenditure and reduced adiposity. Although this study showed positive results, there are still limitations in controlling external factors such as stress levels that may affect leptin levels. Further research is recommended to consider these variables so that the results are more comprehensive.